Can East Asia Weather a US Slowdown? - Cyn-Young Park (Asian Development Bank (ADB), 2007)
The expected slowdown in the economy of the United States (US) has ignited increasing concerns over the short-term growth prospect of East Asia. Historically, a US slowdown has often been associated with a global slowdown. East Asia has been particularly vulnerable to slowing US growth, given its relatively high export reliance on the US market. During the last slump in 2001–2002, a drop in US imports immediately translated into falling exports, cuts in industrial production, and declining growth rates in East Asia. Using the Oxford Economics' Global Model, this paper examines the possible impacts on East Asia of a sharper and longer US slowdown than is currently anticipated by the Asian Development Bank in its Asian Development Outlook 2007. The results of the simulation exercises suggest that the impact of a US slowdown on its own would not significantly impact growth in East Asia. However, if a US slowdown instigates disorderly adjustments in international financial markets and spills over into the People's Republic of China, the remainder of East Asia would not be spared.
hdl:11540/1856
Keywords: 330; Konjunktur; USA; Wirkungsanalyse; Wirtschaftswachstum; Asien